2019
DOI: 10.5507/ag.2019.002
|View full text |Cite
|
Sign up to set email alerts
|

The effects of self-controlled and instructor-controlled feedback on motor learning and intrinsic motivation among novice adolescent taekwondo players

Abstract: augmented feedback during practice may lead the learner to develop a detrimental dependency on this type of feedback. This may result in better performance during practice but weak performance at transfer is an indication of poor motor learning (Salmoni, Schmidt, & Walter, 1984). Recent studies in this context have formulated a particular attitude toward motivational role of augmented feedback for motor learning (Wulf & Shea, 2004). These findings suggest that motivational role of feedback can have a direct ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 41 publications
(72 reference statements)
0
12
0
Order By: Relevance
“…For example, 10-year-old children learnt a beanbag throwing task more effectively when feedback was requested more frequently. Even when feedback is requested at a less than-optimal-rate, the opportunity for choice (i.e., autonomy support) enhanced motor learning, potentially due to increased intrinsic forms of motivation (Chiviacowsky, de medeiros, Kaefer, Wally, & Wulf, 2008;Chiviacowsky, Wulf, de medeiros, Kaefer, & Tani 2008;Goudini, Ashrafpoornavaee, & Farsi, 2019). Notably, adults exposed to similar feedback protocols did not differ in their learning (Chiviacowsky, Godinho, & Tani, 2005), suggesting potential developmental influences where children are particularly sensitive to the role of choice and feedback (Patall et al, 2008).…”
Section: Autonomy Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, 10-year-old children learnt a beanbag throwing task more effectively when feedback was requested more frequently. Even when feedback is requested at a less than-optimal-rate, the opportunity for choice (i.e., autonomy support) enhanced motor learning, potentially due to increased intrinsic forms of motivation (Chiviacowsky, de medeiros, Kaefer, Wally, & Wulf, 2008;Chiviacowsky, Wulf, de medeiros, Kaefer, & Tani 2008;Goudini, Ashrafpoornavaee, & Farsi, 2019). Notably, adults exposed to similar feedback protocols did not differ in their learning (Chiviacowsky, Godinho, & Tani, 2005), suggesting potential developmental influences where children are particularly sensitive to the role of choice and feedback (Patall et al, 2008).…”
Section: Autonomy Supportmentioning
confidence: 99%
“…A manipulation check regarding children's thoughts may have potentially captured this issue and confirmed the direction of attention promoted by the feedback statements. Additionally, the authors propose that augmented information processing explains the self-controlled practice benefits (Carter & Ste-Marie, 2017;Grand et al, 2015) however enhanced information processing is not a suitable alternative explanation (Goudini et al, 2019;Grand, Daou, Lohse, & Miller, 2017;Ikudome, Kou, Ogasa, Mori, & Nakamoto, 2019;Lemos et al, 2017;Ste-Marie et al, 2013). Instead there are likely numerous factors which mediate and moderate the effects of self-control (e.g., the timing of choice; Chiviacowsky & Wulf, 2005).…”
Section: Autonomy Supportmentioning
confidence: 99%
“…In this study, self-control participants requested feedback after only 7% or trials, yet they performed better than all other groups. Goudini et al. (2019) compared the effectiveness of self-controlled, yoked and a 50% instructor-controlled feedback schedule on the acquisition of a taekwondo technique among adolescent athletes.…”
Section: Discussionmentioning
confidence: 99%
“…While this paradigm has been useful for controlling the quantity and temporal presentation of feedback, comparisons of self-controlled conditions with other feedback schedules (e.g., those of varying relative frequency or instructor-controlled feedback) are lacking. To date, there have been only a few investigations comparing self-controlled feedback to schedules other than the yoked condition, and these have produced mixed results (Goudini et al., 2019; Hemayattalab, 2014; Janelle et al., 1995). Thus, there are no clear conclusions regarding the bases of self-control advantages.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been revealed that allowing learners to control the delivery of video feedback can increase self-efficacy [ 16 , 17 , 18 ], technical performance [ 16 , 19 ], task recall [ 20 ] and intrinsic motivation [ 17 , 21 ]. According to Barros et al [ 15 ], limiting how much feedback could be requested seems to increase attention to decisions about feedback and its use.…”
Section: Introductionmentioning
confidence: 99%